Suppression effect of eurycomanone on the growth of HepG2 tumour transplanted in mice - Zakaria, Yusmazura (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Eurycoma longifolia Jack, from the family of Simaroubaceae is commonly distributed in South East Asia including Malaysia. Locally it is known as Tongkat Ali. The plant has achieved a considerable attention for its medicinal properties and traditional claims as treatment of ailments including reduces fever, the concoction is used as tonic for wellness, sexual insufficiency and anti ulcer. A lot of research has been carried out on the plant materials for their scientific evidence as claimed. Eurycomanone is a cytotoxic compound found in Eurycoma /ongifolia Jack. Previous studies had noted the cytotoxic effect of eurycomanone against various cancer cell lines. The aim of the study is to investiga:te the effects of both Eurycoma /ongifolia (crude extract) and eurycomanone, on the growth of xenotransplanted hepatoma cell, HepG2 in nude mice. Nude mice were inoculated with HepG2 cells, subcutaneously in the right flank. When the tumour volume reached 100 mm3 , eurycomanone (6 mglkg and 17 mglkg) was applied intraperitoneally once a day, until 30 days. Crude extract (CE) of Eurycoma longifolia also administered to the mice bearing tumour to compare the effectiveness between CE and eurycomanone. Tumour size in mice-treated eurycomanone at concentration of 17 mglkg significantly reduced, compare to control and CE. 39.9% of relative tumour growth ratio value was calculated with relative tumour volume of 1.5±0.09. Half of the tumour growth was suppressed with 50% inhibition rate was calculated. Growth reduction was associated with significantly reduced mitotic index. Eurycomanone has a great effect in suppressing the growth of HepG2 tumour transplanted in nude mice. Thus it is promising for treatment of hepatocellular carcinoma.